The Impact of Tax Reforms on Economic Justice in Indonesia: Who Benefits from the New System? (Indonesian Economic Justice Review, 2025)
This paper critically analyzes the recent tax reforms in Indonesia, focusing on their impact on economic justice, income inequality, and wealth distribution. In response to fiscal challenges and the need for greater revenue generation, the Indonesian government has implemented significant tax reforms designed to broaden the tax base, improve efficiency, and enhance public sector financing. However, questions remain about who benefits most from these reforms, and whether they contribute to greater social equity. The paper examines key changes, such as adjustments to income tax brackets, the introduction of new taxes on digital services, and revisions to the corporate tax system. Through an analysis of the distributional effects of these reforms, the study explores whether they disproportionately favor the wealthy or multinational corporations while placing a greater burden on low-income households and small businesses. By investigating the implications of these tax policies on income inequality, wealth redistribution, and social mobility, the paper provides a comprehensive assessment of whether Indonesia’s tax reforms contribute to or hinder economic justice. The findings suggest that while the reforms have the potential to increase government revenue and address fiscal deficits, they may require further adjustments to ensure that the tax system promotes a more equitable distribution of wealth.